Risk assessment for oral urgent treatment in Primary Healthcare: a cross-sectional study - Danielle Viana Ribeiro Ramos; João Luiz Miraglia; Camila Nascimento Monteiro; Danielle Borchardt; Leonardo Tribis; Thais Paragis Sanchez; Daiana Bonfim; Danielle da Costa Palacio; Maria da Luz Rosário de Souza; Marília Jesus Batista de Brito Mota (BMC, 2020)
Abstract Background The World Health Organization has advocated for the integration of dental care into the primary healthcare (PHC) setting, including oral urgent treatment (OUT). However, the knowledge necessary for OUT implementation in this setting is still limited. Thus, this study aimed to describe the impact of the implementation of oral disease risk assessment tools for oral health management in PHC. Methods This was a cross-sectional study that included individuals served by a single public PHC unit, with integrated oral healthcare teams, located in the south region of the city of São Paulo, Brazil, between April of 2015 and March of 2017. Data were collected from dental records. Three co-primary endpoints: same day treatment offered, first future appointment scheduled fulfilled, and treatment plan completed were compared before and after the implementation of oral disease risk assessment for OUT. Results A total of 1214 individuals that sought OUT, 599 before and 615 after the implementation of oral disease risk assessment for OUT were included in the study. All three co-primary endpoints had significant changes after the implementation of oral disease risk assessment for OUT. Individuals were significantly more likely to be offered same day treatment after (39.9%; 95% CI:36.0-43.9%) than before (9.4%; 95% CI: 7.2-12.0%), to fulfill their first future appointment scheduled after (34.9%; 95% CI:31.1-38.8%) than before (20.7%; 95% CI: 17.5-24.2%), and to have their treatment plan completed after (14.3%; 95% CI:11.6-17.4%) than before (10.0%; 95% CI: 7.7-12.7%) the intervention. Conclusions This study provided evidence of the positive impact oral disease risk assessment tools could have in the organization of OUT in PHC settings.